Construction of Religious Tolerance: Revitalizing The Prayer of Da'wah on Social Media - Prasetyo Nugroho, Adhitya Ridwan Budhi; Nawawi (Fakultas Dakwah UIN Saizu Purwokerto, 2023)
Social conflicts resulting from differences in religious beliefs and beliefs need to be managed to resolve differences and build lasting consensus. Therefore, the issue of harmony between religious and cultural communities and existing beliefs, both locally and nationally, is a big problem that cannot be ignored and needs serious attention from all parties. Therefore, if religious conflict occurs frequently, it can destroy human values and the foundation of human life. The method used in this research is qualitative with a literature study approach. The results of this research are that people have the freedom to consume whatever form of media they like, but the media itself must function as a filter in deciding what news to cover so that it can function as a social glue for issues such as religious tolerance. The existence of the media as a means of disseminating information demands responsibility to society. Misuse of social events in the media will have a negative impact on society. The existence of the media as a means of disseminating information demands responsibility to society. Misrepresenting social events in the media can potentially have devastating consequences for society.